Respondent Judgment Analysis on the Weighted Value of Political, Economic, Social and Defense Factors in Indonesia to Face the Development of the Industrial Revolution 5.0 and the Global World - Ferri Susanto; Syukri Hamzah (Nusantara Education, 2023)
This research focuses on assessing the weight of political, economic, social and defense and security factors which continuously develop dynamically along with the development of the global world which continues to experience revolutionary changes starting from the industrial revolution 4.0 to the present towards the industrial revolution 5.0. The purpose of this study was to measure the weight of the importance of several objects that had been observed based on the judgment of 6 respondents who were competent in their field. Simple data calculation, namely the weighting method which is also known as the Analytical Hierarchy Process method or often referred to as the weighting method which is a combination of qualitative and quantitative meaning that this method will later use comparisons. By identifying the factors that need to be analyzed, making comparisons of the respondent's factor values, assessing each factor with the principle of the higher the value or weight, making a matrix for each respondent, then compiling the average matrix by adding up each factor's opinion of the respondents then dividing by the number responders and normalize. Weighting on each factor. Based on the results of the calculation of the weighting assessment in this study, namely Political factors obtained by 25.84%, Economic by 23.97%, Social by 24.35% and Defense and Security by 25.83%. Political factors have the highest weighting assessment, namely 25.84% so that it can be concluded that political factors have the greatest impact and are at the same time factors that must be considered in Indonesia at this time. The percentage results for political, social, economic and defense weighting are the basis of strength that must be integrated and synergized with each other so that they are able to face the global changes in the industrial revolution from 4.0 to industrial revolution 5.0, society known as 4C, namely: creativity, critical thinking, communication, and collaboration.